Boundary element techniques for some two-dimensional anisotropic heat conduction problems - Choo, Kin Kei (2008)
With extensive applications of composite materials in engineering, the analysis of heat conduction in such materials with numerical techniques has gained great importance. In this thesis, three different types of two-dimensional heat conduction problems are solved numerically using the Boundary Element Method (BEM).